Effectiveness of Digital Technology on Enhancing Mathematics Achievement of Indonesian Secondary Schools Students’: A Meta-Analysis Research from 2018-2023 - Rahma, Fauziah Annisa; Nurlaelah, Elah (FKIP Universitas Lampung, 2024)
Effectiveness of Digital Technology on Enhancing Mathematics Achievement of Indonesian Secondary Schools Students’: A Meta-analysis Research from 2018-2023. Objective: This study aimed to analyze the impact of digital technology on the mathematics achievement of Indonesian secondary school students through a meta-analysis. Methods: This study used a meta-analytic research design. A comprehensive literature search was conducted through Google Scholar to find relevant studies published from 2018 to 2023. The PRISMA flow diagram documented each stage of study selection, resulting in ten studies meeting the inclusion criteria. Data analysis involved calculating effect sizes using descriptive quantitative and categorizing results into small, moderate, or significant levels to provide a comprehensive summary of digital technology’s impact across various educational levels and mathematics topics. Findings: The analysis revealed that digital technology had a moderate positive effect on students’ overall mathematics achievement, with an average effect size of 0.417. Digital technology was more effective for junior high students with an effect size of 0.499, compared to a lower impact for senior high students with an effect size of 0.091. Among the topics analyzed, “Set” showed the highest effect size at 0.733, while “Limit of Algebraic Functions” exhibited the lowest at 0.136. Conclusion: The meta-analysis revealed that digital technology has a moderate effect on enhancing mathematics achievement among Indonesian secondary students. Digital tools are more effective for visual and conceptual topics than for abstract concepts and benefit junior high students more than senior high students. These findings highlight the need for tailored digital strategies based on content type and student level. Further research should explore features of digital tools that maximize mathematics achievement. Keywords: digital technology, mathematics achievement, secondary school, meta-analysis, Indonesia.DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp803-813